Elasto-Thermodiffusion Modeling Using Optoelectronic Microtemperature Processes for a Ramp-Type Heating Nano-Semiconductor Material - M. Adel; Khaled Lotfy; Alaa El-Bary; M. Ahmed (Journal of Mathematics)
The theory of photo-thermoelasticity describes how heating or elastic microstructure mechanical deformation can modify a material’s optical-thermal properties. This theory particularly highlights the effect of microtemperature on elasticity and efficient heat transport. This work provides a new theoretical framework for thermooptical elastic materials and clarifies the relationship between thermomechanical and plasma waves in microtemperature-affected semiconductors such as silicon. The model focuses on studying the elasto-thermodiffusion (ETD) theory’s electron-hole interaction. Microtemperature effects during photothermal (PT) stimulation are studied in this theory. In one-dimensional (1D) settings, the Laplace transform is utilized which can be solved using the governing equations for thermoelastic (TD) processes and electronic (ED) deformation processes in a nondimensional form. The proposed model is put to use in analyzing how ramp-type heating affects an unbounded semiconductor material plane at rest. The discussion section presents a series of graphs to analyze the effect of the main parameters.